2012
DOI: 10.1111/j.1440-172x.2012.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and practices of school‐aged girls towards menstruation

Abstract: The purpose of this study was to (i) investigate attitude and menstruation-related practices in Jordanian school-aged girls; (ii) identify the influence of premenstrual preparation on girls' attitude and menstruation-related practices. A descriptive cross-sectional design was used. Data was collected from a convenience sample of 490 school-age girls (12-18 years) from different districts in Jordan. Self-report instruments [Menstrual Attitude Questionnaire (MAQ), and Menstrual Practices Questionnaires (MPQ)] we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
2
32
1
2
Order By: Relevance
“…Important new insights were revealed regarding the roles of parents in contributing to girls' fear and confusion around menarche, the tremendous secrecy around menses in select contexts and the global nature of insufficient MHM guidance. While some of these findings resonate with those of recent peer-reviewed studies and reports from the grey literature (Crofts and Fisher 2012;Fehr 2010;Jarrah and Kamel 2011;McMahon et al 2011;Sommer 2009a; Sommer and Ackatia-Armah 2012; WaterAid 2009), additional research is needed to better understand country-specific menstrual etiquette, reinforcement of gendered behaviours, and physical and social challenges for girls in the school environment that emerged from these four studies.…”
Section: Discussionsupporting
confidence: 73%
“…Important new insights were revealed regarding the roles of parents in contributing to girls' fear and confusion around menarche, the tremendous secrecy around menses in select contexts and the global nature of insufficient MHM guidance. While some of these findings resonate with those of recent peer-reviewed studies and reports from the grey literature (Crofts and Fisher 2012;Fehr 2010;Jarrah and Kamel 2011;McMahon et al 2011;Sommer 2009a; Sommer and Ackatia-Armah 2012; WaterAid 2009), additional research is needed to better understand country-specific menstrual etiquette, reinforcement of gendered behaviours, and physical and social challenges for girls in the school environment that emerged from these four studies.…”
Section: Discussionsupporting
confidence: 73%
“…A study done on comparison of the menstruation and education experiences of girls in Africa reported 84% of girls in Afghanistan never wash their genital areas, where as 80% of girls in Afghanistan use water but no soap for washing their menstrual protection and 30% of girls in Malawi do not use the latrine when menstruating. This was also noted by 20% of women in communities in India [12,13]. A study in Nigeria on the practice of menstrual hygiene of girls 73 (60%) changed sanitary pads three times a day,whereas similar studies reported 11% of girls in Ethiopia and 60% of girls in India only change their menstrual cloths once a day [2,14].…”
Section: Introductionmentioning
confidence: 96%
“…7e9 This is partly due to the fact that menstrual issues, including menstrual pain and abnormal menstrual flow, are considered socially taboo subjects. 3,10 Thus, population studies on the normal and abnormal features of menstruation and its related health problems are scarce in Arab societies. However, knowledge on this issue is necessary for patient education and to guide clinicians and health care providers towards the best possible clinical outcome.…”
Section: Introductionmentioning
confidence: 99%